Familial Hypercholesterolemia-Risk-Score: A New Score Predicting Cardiovascular Events and Cardiovascular Mortality in Familial Hypercholesterolemia. Issue 10 (26th August 2021) - Paquette, Martine; Bernard, Sophie; Cariou, Bertrand; Hegele, Robert A.; Genest, Jacques; Trinder, Mark; Brunham, Liam R.; Béliard, Sophie; Baass, Alexis
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Familial hypercholesterolemia (FH) is associated with a high risk of premature atherosclerotic cardiovascular disease (ASCVD). However, this risk is highly heterogeneous and current risk prediction algorithms for FH suffer from limitations. The primary objective of this study was to develop a score predicting incident ASCVD events over 10 years in a large multinational FH cohort. The secondary objective was to investigate the prediction of major adverse cardiovascular events and cardiovascular mortality using this score. Approach and Results: We prospectively followed 3881 patients with adult heterozygous FH with no prior history of ASCVD (32 361 person-years of follow-up) from 5 registries in Europe and North America. The FH-Risk-Score incorporates 7 clinical variables: sex, age, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, hypertension, smoking, and lipoprotein (a) (Lp(a)) with a Harrell C-index for 10-year ASCVD event of 0.75, which was superior to the SAFEHEART-RE (Spanish Familial Hypercholesterolemia Cohort; 0.69). Subjects with an elevated FH-Risk-Score had decreases in 10-year ASCVD-free survival, 10-year major adverse cardiovascular event-free survival, and 30-year survival for CV mortality compared with the low-risk group, with hazard ratios of 5.52 (3.94–7.73), 4.64 (2.66–8.11), and 10.73 (2.51–45.79), respectively. The FH-Risk-Score showed a similar performance in subjects with and without an FH-causing mutation. Conclusions: The FH-Risk-Score is a stronger predictor of future ASCVD than the SAFEHEART-RE and was developed in FH subjects with no prior cardiovascular event. Furthermore, the FH-Risk-Score is the first score to predict CV death and could offer personalized cardiovascular risk assessment and treatment for patients with FH. Future studies are required to validate the FH-Risk-Score in different ethnic groups.